Selected properties of geopolymers with different portions of ground fly-ash - Želinková, Miroslava (GeoScience Engineering, 2015)
Geopolymers are polymeric materials resulting from the polycondensation reaction of alumino-silicate materials in a strongly alkaline environment. In the consequence, stable polymeric networks of aluminosilicates are formed. The binding potential of FA (fly ash) amorphous component can also be “activated” by mechanical activation, which unfolds new possibilities of FA utilization. Mechanical activation, as a method which can improve FA reactivity, is often applied for different applications for geopolymers based on ground fly ash. This paper presents possibilities of preparing of geopolymer mixtures based on modified (ground) FA (TEKO – produced by the Heating plant Kosice), which was used in varying percentages to unground (original) FA. The particle size of original unground FA (PVT) was 84.7μm and particle size of ground FA (T60S1) was 52.8μm. Properties to be evaluate were selected from expected application point of view – protective coating of concrete. Next properties of geopolymer mixtures after 28 days of hardening were tested and evaluated: dry density, absorptivity, capillarity, compressive and flexural strength.